Perancangan Konsep Sistem Pencatatan Persediaan Berbasis Digital Pada UMKM di Kota Manado - Tangon, Joseph; Tuerah, Raykes Hinrich; Maryadi, Dominikus Andreo; Maluw, Fandel; Rombot, Raymond F; Toweula, Alpindos; Ratag, Johana (LPPM Institut Pendidikan Nusantara Global, 2025)
Difficulties in obtaining information regarding inventory stock and in generating reports for incoming and outgoing goods have become persistent challenges for companies. To address these issues, an information system that meets the company's informational needs is required. This study aims to design a web-based inventory information system. In response to these challenges, it is necessary to develop a digital inventory recording system that is easily accessible, user-friendly, and relevant to the conditions of micro, small, and medium enterprises (MSMEs). The system should be capable of automating the recording process of incoming and outgoing goods, sending notifications when stock reaches the minimum threshold, and generating reports to support inventory planning and control. Given this background, the central research question is: How can a digital inventory recording system be designed for MSMEs in Manado City? A digital-based accounting information system can assist businesses, particularly MSMEs, in presenting reliable information in an effective, efficient, affordable, and user-friendly manner. The Waterfall model is a traditional method used in information system development. This method follows a sequential and structured process, starting from requirement analysis, system design, implementation, testing, to maintenance and updates. The proposed digital inventory recording system can assist MSMEs in tracking stock accurately, efficiently, and in real time. Features such as notifications, automated reporting, and a simple interface make this system easy to use and well-suited for the needs of small businesses. Additionally, the system is designed to support future digital integration.